2009
DOI: 10.1002/jmri.21799
|View full text |Cite
|
Sign up to set email alerts
|

Study of reproducibility of human arterial plaque reconstruction and its effects on stress analysis based on multispectral in vivo magnetic resonance imaging

Abstract: Purpose:To quantify the uncertainties of carotid plaque morphology reconstruction based on patient-specific multispectral in vivo magnetic resonance imaging (MRI) and their impacts on the plaque stress analysis. Materials and Methods:In this study, three independent investigators were invited to reconstruct the carotid bifurcation with plaque based on MR images from two subjects to study the geometry reconstruction reproducibility. Finite element stress analyses were performed on the carotid bifurcations, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…The fibrous cap area influenced by the one-pixel thickness assignment for the 8 symptomatic patients was around 14.1% of the total fibrous cap area, while for the 2 asymptomatic patients the average area was 10.2%. Therefore FCT and FPS values could be overestimated and underestimated, respectively, for symptomatic patients (Gao et al, 2009a). The result that FPS was significantly higher in symptomatic group than asymptomatic group might not be influenced by the fibrous cap segmentation uncertainties in the current study.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…The fibrous cap area influenced by the one-pixel thickness assignment for the 8 symptomatic patients was around 14.1% of the total fibrous cap area, while for the 2 asymptomatic patients the average area was 10.2%. Therefore FCT and FPS values could be overestimated and underestimated, respectively, for symptomatic patients (Gao et al, 2009a). The result that FPS was significantly higher in symptomatic group than asymptomatic group might not be influenced by the fibrous cap segmentation uncertainties in the current study.…”
Section: Discussioncontrasting
confidence: 50%
“…Recent developments in high-resolution multi-spectral MRI have allowed plaque components to be visualized in-vivo (Hatsukami et al, 2000;Cai et al, 2002;Yuan et al, 2002), providing more realistic plaque geometries for stress analysis (Touze et al, 2007;Gao et al, 2009a). Based on 2D in-vivo MRI, Li et al (2007) found that stress in asymptomatic patients was lower than that in symptomatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The current clinically achievable resolution of in vivo MRI is a limiting factor in measuring submillimeter features such as thin FCs, which are especially present in vulnerable plaques [11,15,19,23,24]. This raises concern, because the sensitivity of biomechanical FEA plaque models to FC thickness is very high [13,14,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Carotid magnetic resonance imaging (]VIRI) is the method of choice to obtain the piaque composition and geometry in vivo noninvasively through image segmentation [17,18]. This makes ]VIRI-based FEA a promising methodology to better assess patient-specific carotid plaque vulnerability noninvasively, and numerous studies have utilized MRI-based FEA for carotid plaque [11,15,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The reproducibility of the biomechanical stress simulations has been determined previously by our group. 25 …”
Section: Mesh Generation Computational Models and Solution Methodsmentioning
confidence: 99%